2014
DOI: 10.1093/dnares/dsu035
|View full text |Cite
|
Sign up to set email alerts
|

Integrative structural annotation of de novo RNA-Seq provides an accurate reference gene set of the enormous genome of the onion (Allium cepa L.)

Abstract: The onion (Allium cepa L.) is one of the most widely cultivated and consumed vegetable crops in the world. Although a considerable amount of onion transcriptome data has been deposited into public databases, the sequences of the protein-coding genes are not accurate enough to be used, owing to non-coding sequences intermixed with the coding sequences. We generated a high-quality, annotated onion transcriptome from de novo sequence assembly and intensive structural annotation using the integrated structural gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 52 publications
(48 reference statements)
2
49
0
Order By: Relevance
“…Only 15% to 49% of the highly abundant transcripts identified by this study were similar to those previously identified in bulb onion [810, 23], highlighting the value of our multiple organ transcriptome assembly. The half of the transcripts from this transcriptome assembly were present in an assembly from six week old seedling short and long day onions [23].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Only 15% to 49% of the highly abundant transcripts identified by this study were similar to those previously identified in bulb onion [810, 23], highlighting the value of our multiple organ transcriptome assembly. The half of the transcripts from this transcriptome assembly were present in an assembly from six week old seedling short and long day onions [23].…”
Section: Resultssupporting
confidence: 65%
“…The half of the transcripts from this transcriptome assembly were present in an assembly from six week old seedling short and long day onions [23]. Also in garlic, 78% of transcripts generated in multiple organ transcriptome were present in the transcriptome developed from single tissue [22, 24].…”
Section: Resultsmentioning
confidence: 99%
“…We then annotated the representative loci by BLASTP (e-value ≤ 1e −08 ) against melon (CM V3.5) and Arabidopsis genes (TAIR 10), as reported previously (Kim et al, 2016a). Furthermore, we also performed ISGAP pipeline to determine more precise transcripts by removing intron contaminants (Kim et al, 2015). Of the representative loci, 35,364 were assigned to melon reference proteins, and 33,963 were assigned to Arabidopsis proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The quality-checked sequence reads from different tissue samples were assembled de novo using two software tools based on de Bruijn graphs: Velvet (v1.2.07) (Zerbino & Birney, 2008) and Oases (v0.2.08) (Schulz et al, 2012). The assembled transcripts were used for DEG extraction or functional annotation by edgeR or BLASTP with Cucumis melo or Arabidopsis thaliana as queries (Kim et al, 2015; Klukas & Schreiber, 2007). The annotated genes were used for further analyses including gene ontology (GO) and KEGG analyses.…”
Section: Methodsmentioning
confidence: 99%
“…To compare A. fistulosum unigenes with those from other Allium species, sequence datasets were downloaded from the NCBI Transcriptome Shotgun Assembly database (http://www.ncbi.nlm.nih. gov/genbank/tsa/) with the following accession numbers: garlic, TSA JV230866-JV310008; bunching onion, TSA FX553726-FX608587 and FX657476-FX657516; and onion, GBRQ01000000 (Sun et al 2012;Tsukazaki et al 2015;Kim et al 2014).…”
Section: Sequence Annotationmentioning
confidence: 99%